Postoperative and long-term survival in relation to life-expectancy after pancreatic surgery in elderly patients (cohort study). (September 2021) - Burgdorf, S.K.; Storkholm, J.H.; Chen, I.M.; Hansen, C.P.
Abstract: Background: An evaluation of the outcome after pancreatic surgery with focus on post-operative and late survival in elderly patients was performed. Methods: The study included 1.556 patients from a single HBP unit operated from 1. January 2010 to 31. December 2019. Patients were divided into two cohorts, < 75 years ( n = 1.296) and ≥75 years ( n = 260). Post-operative outcome was evaluated in all patients and late outcome in patients with adenocarcinoma in the pancreas ( n = 765) and the duodenum ( n = 117). The follow-up of patients with benign disease and adenocarcinoma was 57.95 (12.1–132.7) and 39.85 (12.0–131.7) months, respectively. Results: Length of hospital-stay and surgical complications were not significantly different in the two cohorts, but in-hospital death was 1.1% (<75 years) and 3.5% (≥75 years) ( p = 0.008). The median overall survival of adenocarcinoma was 29.7 (<75 years) and 24.3 months (≥75 years) ( p = 0.3228) with a one, two, and five-years survival of 74.5%, 56.6% and 28.6% vs. 73.6%, 51.1%, and 25.5%. Median time to relapse (46.2% of patients <75 years and 40.5% of patients ≥75 years) was 9 (1 - 51) and 8 (1 - 78) months (p = 0.534), respectively. Adjuvant chemotherapy did not have impact on the survival of the old cohort. Patients who died during the observation period had lost 94% (<75 years) and 87% (≥75 years) of expected remnant life. Estimated years lost in the old cohort was 4.2 in males and 4.9 in females ( p = 0.025) Conclusion: Elderly patients may undergo pancreatic surgery with a low mortality and for adenocarcinoma with an acceptable long-term survival. Highlights: Surgery is the only potentially curable treatment to pancreatic cancer. Elderly patients may tolerate pancreatic surgery with low mortality. Radical pancreatic surgery improves long-term survival, also in elderly patients. Operability should be evaluated from morbidity and biological age. Pancreatic surgery in elderly should only be performed in high volume centers.